MBT AS THERAPEUTIC SHOE FOR ANKLE INSTABILITIES - Magdalena Sütő; Danelciuc Francisc Tadeus (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Top priority in the treatment of chronic ankle instability is given to the optimum strengthening of the muscles surrounding the ankle joint -- initially in physiotherapeutic sessions, later in daily training -- so that the malfunction of the ligaments can be dynamically compensated and the ankle joints can be functionally re-stabilised.